Corruption and control from the perspective of Islam - Alazzabi, Waled Younes; Mustafa, Hasri; Abdul Latiff, Ahmed Razman (Emerald Publishing, 2020)
Purpose: The purpose of this paper is to explore and provide insights into corruption and the control procedures from an Islamic perspective. Design/methodology/approach: This paper adopts qualitative research approach using the holy Quran as a primary source and hadith of the Prophet Mohammed supported by the anecdotes of his companions as a secondary source and prior literature. Findings: This paper offers an Islamic taxonomy of corruption that contains economic, managerial, financial, political, environmental, social and ethical corruption which is explicitly prohibited because of their consequence on societies. Islam establishes proactive, preventive, detecting and reactive procedures to control corruption and prescribes how to avoid its harmful consequences. The paper also reveals significant concepts in relation to individuals’ qualities that if taken care of, better chances to reduce corruption and better living conditions can be accomplished. Research limitations/implications: The paper recommends means to the business community through providing managerial and practical procedures which can be used for limiting corruption effectively. However, this piece of work provides further explanations on corruption to improve our understanding on such a phenomenon and contributes to the literature from the perspective of Islam point of view. Originality/value: The paper contributes to the debate on corruption, human, religion and control from an Islamic point of view, which is lacking. This paper finds evidence that loss of belief is a situational factor that leads to corrupt acts. Also, moral teaching in early ages is necessary for inner and self-control. Moral renovation is an influential factor that keeps individuals motivated and refrain from indulging into corrupt acts.